Social and Epidemiological Diagnosis in Biru Village, Yogyakarta, using Community Diagnosis Approach - Rochana Ruliyandari; Brilly Annisa Asdiany (Jurnal Cakrawala Promkes, 2022)
Backround: Health in the community is formed from the closest and smallest environment, namely the family. Supported by the surrounding environment such as residence, school, workplace, and friends. Objective: This study will analyze the health problems that occur, especially in 31 families in Dusun Biru, Yogyakarta, Indonesia. After being analyzed, suggestions will be given to seek solutions to health problems that occur. Methods: The method used in this study is quantitative with a scoring technique. Previously, interviews would be conducted using a community diagnosis approach. Results: Data showed that 1 person was diagnosed with ARI (infectious disease) and 26 others had non-communicable diseases such as asthma (2), diabetes mellitus (9), heart disease (1), hypertension (12), and stroke (2). Conclusion: The highest health problems are hypertension and diabetes mellitus. Therefore, family support is needed to change a healthier lifestyle